Respuesta :

Answer: [tex](gof)(-1)=-2[/tex]

Step-by-step explanation:

By definition, a composite function is a function formed by substituing one function into another function.

Given the composite function:

[tex](gof)(-1)[/tex]

You can rewrite it in the following form:

[tex]g(f(-1))[/tex]

In order to evaluate it, follow these steps:

- Based on the table of the function f(x), the ouput value for [tex]x=-1[/tex] is [tex]y=3[/tex]. Then:

[tex]f(-1)=3[/tex]

- This will be the input of the function g(x).

- Notice in the table of the function g(x) that the output value when [tex]x=3[/tex] is [tex]y=-2[/tex]:

[tex]g(3)=-2[/tex]

Therefore:

[tex]g(f(-1))=-2[/tex] or [tex](gof)(-1)=-2[/tex]

Answer:

The value of [tex]\rm{gof(-1)}[/tex] is -2.

Step-by-step explanation:

Given,

The table contains the functional value of f(x) and g(x).

To find:   [tex]\rm{gof(-1)}[/tex]

[tex]\rm{fog(-1)}[/tex] is a composite function of f(x) and g(x).

[tex]\rm{gof(-1)}=\rm{g[f(-1)}][/tex]

Clearly from the table, the value of f(x) when [tex]x=-1[/tex] is 3.

Therefore,

[tex]f(-1)=3[/tex]

Now,

[tex]\rm{gof(-1)}=\rm{g[f(-1)}]\\\rm{fof(-1)}=\rm{g(3)}[/tex]

Clearly from the table, the value of g(x) when [tex]x=3[/tex] is -2.

Thus,

[tex]\rm{gof(-1)}=-2[/tex]

To know more, please refer to the link:

https://brainly.com/question/18839694?referrer=searchResults

ACCESS MORE